Oocyte vitrification for elective fertility preservation: the past, present, and future. Issue 1 (February 2017) - Gunnala, Vinay; Schattman, Glenn
Abstract : Purpose of review: Oocyte cryopreservation is no longer experimental and one of its rapidly growing indications is elective fertility preservation. Currently there is no sufficient evidence to support its practice and therefore its place in IVF remains uncertain. Recent findings: Vitrification has superior post-thaw survival and fertilization outcomes compared with oocytes that were frozen with the slow-freeze technique. Oocyte vitrification produces similar IVF outcomes compared with fresh oocytes and is not associated with further obstetrical or perinatal morbidity. Undergoing elective oocyte cryopreservation between ages 35 and 37 will optimize live birth rates as well as cost effectiveness from mathematical models. Summary: In women who delay child bearing, elective oocyte cryopreservation in the mid 30s may be beneficial in terms of live birth rates and cost effectiveness. Prospective studies of women who have undergone oocyte cryopreservation and are now attempting conception are needed before official recommendations can be made regarding elective egg freezing.